Risk factors for carpal tunnel syndrome or trigger finger following distal radius fracture: a nationwide study - Yeh, Kuang-Ting (Sci Rep, 2020)
New-onset carpal tunnel syndrome (CTS) and trigger finger after distal radius fractures (DRFs) with or without open reduction and internal fixation (ORIF) have been reported inconsistently across different studies. This study assessed the incidence of CTS and trigger finger after DRFs using Taiwan National Health Insurance Research Database. In total, 1454 patients in the case (ORIF) cohort and 1454 patients in the control (non-ORIF) cohort were included in this retrospective study. The mean age was approximately 55 years old, and the female to male ratio was approximately 3/2. Nine patients underwent carpal tunnel release (CTR) surgery after diagnosis of CTS in the case group, and no patients did in the control group; whereas 19 cases of CTS were diagnosed without CTR in the case group, and 4 such cases were observed in the control group. Five cases of trigger finger were diagnosed in the case group, and 3 cases were diagnosed in the control group. CTS were significantly associated with ORIF for DRFs within 9 months after the fracture, whereas trigger finger was not significantly different between groups. Diabetes mellitus was a significant risk factor for CTS and trigger finger within 9 months after the incidence of DRFs.